2016
DOI: 10.1016/j.scitotenv.2015.12.134
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of soil erosion and suspended sediment dynamics in the Mekong River Basin

Abstract: Understanding of the distribution patterns of sediment erosion, concentration and transport in river basins is critically important as sediment plays a major role in river basin hydrophysical and ecological processes. In this study, we proposed an integrated framework for the assessment of sediment dynamics, including soil erosion (SE), suspended sediment load (SSL) and suspended sediment concentration (SSC), and applied this framework to the Mekong River Basin. The Revised Universal Soil Loss Equation (RUSLE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…However, the relative error (RE) for the entire validation dataset of the model is approximately 43%, with a RE of 44% and 41% for dry season and wet season samples respectively. While this RE is above the desired value RE of 35% set by NASA's Ocean Biology and Biogeochemistry Program [65], we are confident in our model because this relative error corresponds to a root-mean-square error ( Previous studies of suspended sediment in the Lower Mekong Basin (using both in situ and remote sensing approaches) have focused largely on the mainstem water quality stations [8,27,34]. In this study we used all available data (mainstem and tributaries) to develop a empirical model of SSSC that can be applied throughout the entire basin.…”
Section: Model Calibration and Validationmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the relative error (RE) for the entire validation dataset of the model is approximately 43%, with a RE of 44% and 41% for dry season and wet season samples respectively. While this RE is above the desired value RE of 35% set by NASA's Ocean Biology and Biogeochemistry Program [65], we are confident in our model because this relative error corresponds to a root-mean-square error ( Previous studies of suspended sediment in the Lower Mekong Basin (using both in situ and remote sensing approaches) have focused largely on the mainstem water quality stations [8,27,34]. In this study we used all available data (mainstem and tributaries) to develop a empirical model of SSSC that can be applied throughout the entire basin.…”
Section: Model Calibration and Validationmentioning
confidence: 55%
“…Previous efforts to estimate SSSC and TSS from remote sensing data sources in the Lower Mekong Basin have focused on the main stem of the Mekong River or on the Mekong Delta, but not both. For example, Suif et al [34] developed an empirical model using the near-infrared band on Landsat TM as well as the blue, green, and red bands in a multiple linear regression along the Mekong River. In another recent study, Duc et al [35] found a strong correlation between the 1st principle component of Landsat TM and ETM+ imagery and SSSC in the Mekong Delta.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that approximately one-third of the global sediment load to oceans is generated from the large rivers originating from the Tibetan Plateau and its neighboring regions [2]. In recent decades, the sediment regimes of these rivers have attracted increasing attention due to public concerns about climate change and increasing human activities [3][4][5][6][7][8][9][10][11]. Human activities, such as infrastructure development, soil conservation, and sand excavation, have played an important role in sediment load variations [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Coastal sea and ocean waters are often characterized by a high value of variability in the concentration of Suspended Particulate Matter (SPM) [5]. For detecting suspended sediments events in coastal sea and ocean waters, researchers can use low or high-spatial resolution satellites data such as those provide by: SeaWiFs [4], MERIS [6], GOCI image [7], Landsat [8], Sentinel-3 [9], MODIS [10]-Aqua and Terra [11]. In particular, multispectral sensors like MODIS offer a high number of spectral bands to detect, identify, classify, describe and guarantee daily image frequency [12].…”
Section: Introductionmentioning
confidence: 99%